Disturbance and indirect effects of climate warming support a plant invader in mountains. Issue 4 (3rd February 2022) - Haider, Sylvia; Palm, Sebastian; Bruelheide, Helge; de Villemereuil, Pierre; Menzel, Annette; Lachmuth, Susanne
Abstract : Climate warming and increased disturbance (resulting from intensified land use) are expected to enhance the invasibility of plant communities and the performance of exotic species also at high elevations, and thus pose additional threats to mountain ecosystems. The invasion success of introduced genotypes will also depend on their degree of pre‐adaption to high elevation climatic conditions, which may vary intra‐specifically across source populations. For populations currently spreading in the lowlands, climate warming might reduce the climatic distance to high‐elevation sites and thus remove a barrier to upwards spread. Here, we investigated the various facets of mountain invasions in a single, integrative experimental study. We applied a community transplant approach between high‐ and low‐elevation sites in the European Alps to address effects of climate warming and disturbance through land use on community invasibility and the performance of the exotic species Senecio inaequidens, a potential future plant invader in the Alps. Additionally, the transplant sites served as common gardens to test the influence of climatic pre‐adaptation to current (high site) and future (low site) climatic conditions on the performance of S. inaequidens in the transplanted communities. The 16 invasive central and western European S. inaequidens source population locations covered a wide geographic range, and thus a wide amplitude of climatic distances and presumed pre‐adaptation to our gardens. Our results attest to a strong effect of disturbance, which increased community invasibility, and promoted the performance of the exotic species. Contrary to our expectation, experimentally induced climate warming did not increase community invasibility. However, the performance of the S. inaequidens populations was positively related to their pre‐adaptation to the climatic conditions of our common gardens. Climate warming might thus promote the invasion of exotic species by reducing the climatic distance between mountain ranges and locations of potential source populations.